HANDLING COVID-19 PANDEMIC CRISIS TO SUSTAIN THE HOTELS BUSINESS - Trongjitraksa, Suanghatai; Batra, Adarsh (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Crisis management is a necessary factor in successful digital tactics. In the crisis period, the hospitality industry needs to think wisely to develop a prevention plan quickly, communicate with employees and guests, and make critical shifts to successful revenue management and digital strategy. The study aims to understand the impact of Covid-19 on the hotel industry and to summarize how hotels handle with this pandemic situation. As well as, this study is focusing on what kind of prevention that hotels use to handle with Covid-19 pandemic, what are the recovery process and plan that hotels use to sustain the business after the crisis, and what strategies hotels applied to manage within the organization. The researcher chose a qualitative method with an in-depth interview to collect information from asking 15 questions. The data was collected from eight hotels based in Bangkok and Chonburi province with nine managers. The collection data doing were done from June 22, 2020 to July 8, 2020. The Thematic Analysis technique was applied to analyze. According to this study, the researcher found that Artificial Intelligence is very helpful for back of the house of hotel for productive, validity and capacity and Keep in touch to customer is very necessary to remind them and not forget them. They will feel impress with every massage, email, and call from hotels. Keywords: Covid-19 pandemic, Artificial Intelligence, and robotics, Hotel